Paleoecology and paleoceanography of the Athel silicilyte, Ediacaran–Cambrian boundary, Sultanate of Oman. Issue 3 (7th April 2017) - Stolper, D. A.; Love, G. D.; Bates, S.; Lyons, T. W.; Young, E.; Sessions, A. L.; Grotzinger, J. P.
Abstract: The Athel silicilyte is an enigmatic, hundreds of meters thick, finely laminated quartz deposit, in which silica precipitated in deep water (>~100–200 m) at the Ediacaran–Cambrian boundary in the South Oman Salt Basin. In contrast, Meso‐Neoproterozoic sinks for marine silica were dominantly restricted to peritidal settings. The silicilyte is known to contain sterane biomarkers for demosponges, which today are benthic, obligately aerobic organisms. However, the basin has previously been described as permanently sulfidic and time‐equivalent shallow‐water carbonate platform and evaporitic facies lack silica. The Athel silicilyte thus represents a unique and poorly understood depositional system with implications for late Ediacaran marine chemistry and paleoecology. To address these issues, we made petrographic observations, analyzed biomarkers in the solvent‐extractable bitumen, and measured whole‐rock iron speciation and oxygen and silicon isotopes. These data indicate that the silicilyte is a distinct rock type both in its sedimentology and geochemistry and in the original biology present as compared to other facies from the same time period in Oman. The depositional environment of the silicilyte, as compared to the bounding shales, appears to have been more reducing at depth in sediments and possibly bottom waters with a significantly different biological community contributing to the preserved biomarkers. We propose a conceptual model for this system in which deeper, nutrient‐rich waters mixed with surface seawater via episodic mixing, which stimulated primary production. The silica nucleated on this organic matter and then sank to the seafloor, forming the silicilyte in a sediment‐starved system. We propose that the silicilyte may represent a type of environment that existed elsewhere during the Neoproterozoic. These environments may have represented an important locus for silica removal from the oceans.